Ventricular endomyocardial mitochondrial impairment and inflammation accompany diastolic dysfunction in the type 2 diabetic human heart. (25th November 2020) - Zweck, E; Scheiber, D; Jelenik, T; Bonner, F; Horn, P; Pesta, D; Schultheiss, H.P; Boeken, U; Akhyari, P; Lichtenberg, A; Roden, M; Kelm, M; et al.
Abstract:  : Type 2 Diabetes Mellitus (T2DM) is a major risk factor for chronic heart failure, even independent of coronary artery disease. Various underlying mechanisms worsening ventricular function in T2DM have been postulated based on data from animal studies, including mitochondrial abnormalities, alterations of Nuclear factor kappa-B (NfκB) expression, increased oxidative stress and inflammation and cardiac fibrosis and diastolic impairment. However, evidence in humans for these mechanisms is currently lacking. Especially early T2DM-related alterations and the impact of T2DM in the absence of coronary artery disease remain unclear. We hypothesize that T2DM (I) leads to distinct changes in diastolic cardiac function, (II) impairs mitochondrial function of the ventricular myocardium, and (III) increases ventricular myocardial NfκB expression. Heart transplant recipients with T2DM ("T2DM", n=17) and without ("Non-DM", n=32) T2DM (as determined by oral glucose tolerance tests) were included, if they had received their heart from a donor without Diabetes Mellitus. Thus, diabetes-exposure of the transplanted hearts exactly corresponded to the time since transplantation. Magnetic resonance imaging was performed to assess left ventricular ejection fraction, global longitudinal strain (GLS), diastolic strain, and T2 relaxation times, a marker of myocardial edema. We assessed NfκB p105 subunit (NfκB1) mRNA expression using real-time PCR and myocardial mitochondrial respiration using high-resolution respirometry in ventricular endomyocardial biopsies. All participants had normal left ventricular ejection fraction (LVEF) without angiographic signs of coronary artery disease post transplantation (average 2.9±2.4 years). Age, sex distribution and LVEF were comparable between T2DM and Non-DM participants (p=0.50, 0.40 and 0.36, respectively). While GLS was not different (p=0.34), T2DM exhibited lower diastolic strain (1.0±0.4 vs. 1.4±0.4s-1, p<0.01) and higher T2 relaxation times (67±3 vs. 64±3ms, p<0.05) than Non-DM, indicating impaired diastolic function and increased myocardial edema. In T2DM, myocardial mitochondrial respiration with fatty acids and glycolytic substrates was 22–27% lower and mitochondrial uncoupling was 19% higher, whereas ORP and TBARS were 17% and 34% higher than in Non-DM (all p<0.05). Myocardial oxidative capacity related negatively to fasting blood glucose (r=−0.35; p<0.01), and positively to insulin sensitivity (r=0.49; p<0.05) across all participants. Myocardial NfκB mRNA expression was 60% higher in T2DM (0.45 [0.29; 0.71] vs. 0.28 [0.21; 0.44] AU, p<0.05) and correlated inversely with complex I respiration (r=−0.33; p<0.05). Exposure to T2DM diminishes mitochondrial function in ventricular myocardium, which relates to hyperglycemia, insulin resistance, oxidative stress, inflammation, and ventricular diastolic dysfunction and edema. These changes appear within short-term overt diabetes and might precede T2DM-related heart failure. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): This work was supported by funding from the German Research Council (SFB1116) and a grant provided by the research commission of the Medical Faculty, Heinrich-Heine University, Düsseldorf, Germany.